ПАРАЛИМПИЯ ҲАРАТИНИНГ КЕЛИБ ЧИҚИШИ ВА РИВОЖЛАНИШИНИНГ ИЖТИМОИЙ-ҲУҚУҚИЙ АСОСЛАРИ - К.Х.Шамуратов (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
this article analyzes the socio-legal basis of the origin and development of the Paralympic movement at the international and regional level, as well as provides a number of information on the work carried out in this field in the Republic of Uzbekistan.